2005
DOI: 10.2169/internalmedicine.44.1051
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-onset Primary Biliary Cirrhosis Resembling Drug-induced Liver Injury

Abstract: A 54-year-old woman was admitted to our hospital because of acute liver injury. Since she had a history of having used a diet product, drug-induced liver injury (DILI) was initially considered. However, the patient was subsequently diagnosed as suffering from primary biliary cirrhosis (PBC) based on the findings of liver histology and serum anti-mitochondrial antibody positivity. Overlap syndrome between PBC and autoimmune hepatitis (AIH) was also suspected, however, serum levels of aspartate aminotransferase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study found that mixed type DILI and PBC had significant differences in elevated transaminases and bilirubin, while cholestatic type DILI and PBC had no significant differences in all biochemical indexes except total protein. Given that DILI patients may also test positive for autoantibodies and there have been reports that DILI can progress into PBC and AIH (autoimmune hepatitis)-PBC overlap syndrome[14] or PBC was misdiagnosed as DILI[15], clinicians should pay more attention to the differential diagnosis of DILI from PBC in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that mixed type DILI and PBC had significant differences in elevated transaminases and bilirubin, while cholestatic type DILI and PBC had no significant differences in all biochemical indexes except total protein. Given that DILI patients may also test positive for autoantibodies and there have been reports that DILI can progress into PBC and AIH (autoimmune hepatitis)-PBC overlap syndrome[14] or PBC was misdiagnosed as DILI[15], clinicians should pay more attention to the differential diagnosis of DILI from PBC in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patients showed rapid elevation in ALT as well as ALP and γ GTP. Sohda et al previously reported a rare case of rapid‐onset PBC. In their case, drug‐induced liver injury (DILI) and overlap syndrome between PBC and auto immune hepatitis (AIH) were suspected at first.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one patient (patient 3) presented with an acute hepatitis-like condition with markedly elevated serum aminotransferases. In PBC, acute presentations have very rarely been reported[ 11 ]. Because acute presentations of an overlapping syndrome, i.e ., autoimmune hepatitis, are common, it has previously been suggested that autoimmune hepatitis might exhibit overlap with the early stage of PBC in PBC patients with acute presentations[ 12 ].…”
Section: Discussionmentioning
confidence: 99%